Effect of limited enzymatic hydrolysis on structure and emulsifying properties of rice glutelin. (December 2016) - Xu, Xingfeng; Liu, Wei; Liu, Chengmei; Luo, Liping; Chen, Jun; Luo, Shunjing; McClements, David Julian; Wu, Lixin
Abstract: The influence of the degree of hydrolysis (DH) on the structure, solubility, rheology, and emulsifying properties of rice glutelin was investigated. Structural properties were characterized using analysis of molecular weight distribution, surface hydrophobicity, intrinsic fluorescence, and Circular Dichroism (CD) spectra. Protein hydrolysis changed molecular weight, increased flexibility, altered surface hydrophobicity, and increased solubility. Oil-in-water emulsions were prepared from rice glutelin with different DH (0.5%, 2%, and 6%) and their stability to storage, pH, salt, and thermal processing was assessed. The storage, pH, salt, and temperature stability of the emulsions increased with decreasing hydrolysis. Emulsions prepared with 2% DH rice glutelin were stable over a range of environmental conditions: pH 7–9; NaCl <100 mM (pH 7); temperatures < 90 °C (pH 7, 0 mM NaCl) studied. These results will facilitate the formulation and production of natural emulsion-based products using rice glutelin as an emulsifier. Graphical abstract: Highlights: Rice glutelin hydrolysates exhibited more flexible structures than native proteins. Label-friendly stable emulsions were prepared from rice glutelin hydrolysates. Emulsion stability depended on the degree of hydrolysis (DH) of rice glutelin. Rice glutelin with 2% DH gave the best emulsion stability.